Evaluation of Educational Administration Bachelor Program At the College of Education , Sultan Qaboos University - Bilqis Galib Al-Sharie (Sultan Qaboos University, 2008)
The aim of the study is to evaluate the bachelor program of Educational Administration. which was designed for school principals working in the Ministry of Education. The evaluation is based on the perceptions of the second patch of principals who graduated in the academic year (2006-2007). The results of the study indicated that: (1) the program enhanced the participants' knowledge, skills, attitudes and leadership skills. (2) some courses were highly theoretical With little practice (3) the program did not include scientific administrative skills, (4) the importance of training school  principals periodically to let them be aware of new trends in their g field, finally (5) the program needs periodical review to be updated and keep up with current development.